Assessing the developmental effects of fentanyl and impacts on lipidomic profiling using neural stem cell models - Cheng Wang; Jinchun Sun; Rohini Donakonda; Richard Beger; Leah E. Latham; Leihong Wu; Shuliang Liu; Joseph P. Hanig; Fang Liu (Experimental Biology and Medicine, 2025)
Fentanyl is a potent and short-acting opioid that is often given to pediatric patients during surgery to relieve pain and as an adjunct to anesthesia. Its effects on the developing brain are yet to be determined. In the present study, commercially available human neural stem cells (NSCs) were used to model the effects of fentanyl on the developing human brain. We determined the dose dependent effects and temporal relationships between fentanyl exposures and NSC health, viability, and differentiation. Markers of mitochondrial health [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetra-zolium bromide (MTT)] and cell death/damage [lactate dehydrogenase (LDH)] were monitored to determine the dose response effects of fentanyl on NSC viability. In addition, lipidomics analysis was conducted to investigate lipid profile changes in differentiated neural cells treated with fentanyl. Fentanyl did not cause a significant increase in LDH release, nor MTT reduction after 24-h exposure at concentrations of 0.5, 1.0, 3.0, 10, or 100 μM, for both NSCs and differentiated neural cells. Lipidomics data showed the top 15 most variable important in projection (VIP) lipid species (the higher the VIP scores, the bigger changes in treated groups vs. controls), including lysophosphatidylcholines (LPCs), lysophosphatidylethanolamines (LPEs), ceramides (CER), cholesterol esters (ChEs) and sphingosine (SPH). The lipidomic data indicate that LPC (16:0), LPC (16:1), LPC (18:1), CER (d18:0_22:0), CER (d18:2_18:0), CER(d18:2_24:1) were significantly increased, and only ChE (24:5) and SPH (d18:1) were significantly decreased in the highest dose group versus control. These data indicated that fentanyl exposure (24-h) did not induce detectable cell death. However, a lipidomic analysis indicated that fentanyl may affect immature neural cell functions through modifying lipid composition and lipid metabolism. These data indicated that despite the absence of clear neurodegeneration, fentanyl may still have a negative impact on the developing brain.